Translucent Zirconia: A Literature Review - Muthanna S. Ahmed; Ali Dh. Malallah; Nadia H. Hasan; Taiseer Sulaiman (University of Mosul, College of Dentistry, 2024)
Aims: Translucent zirconia has emerged as a promising material for aesthetic dental restorations due to its high translucency. Materials and methods: This review explores various methods to enhance its translucency, including aluminum oxide additives, increased lanthanum oxide content, a higher percentage of yttria, reduced grain size, and reduced sintering time. Strategies to minimize pores and impurities are also discussed. Mechanical properties, such as flexural strength and fracture resistance, are critical factors for successful restorations. Results: Comparisons with conventional zirconia and lithium disilicate reveal favorable flexural strength for monolithic translucent zirconia, making it a suitable replacement for enamel. Additionally, the review examines bonding techniques, such as air abrasion, surface conditioning, and laser treatments, to achieve reliable and durable adhesion between translucent zirconia and resin cement. Proper case selection and handling are essential for achieving optimal outcomes. Conclusions: Translucent zirconia presents a promising option for aesthetic restorations, but careful consideration of clinical requirements and further research on bonding techniques are crucial for its successful integration into modern dental practice. Continued advancements and expanded applications are expected as this innovative material continues to evolve in restorative dentistry.